Working with Young Children in Museums Weaving theory and practice - Hackett, Abigail, 1980-; Holmes, Rachel (Rachel D.); MacRae, Christina (London ; New York, NY : Routledge/Taylor & Francis Group, 2020)
Working with Young Children in Museums makes a major contribution to the small body of extant research on young children in museums, galleries and heritage sites. Bridging theory and practice, the book introduces theoretical concepts in a clear and concise manner, whilst also providing inspirational insights into everyday programming in museums. Structured around three key themes, this volume seeks to diverge from the dominant socio-cultural learning models that are generally employed in the museum learning literature. It introduces a body of theories that have variously been called new materialist, spatial, posthuman and Deleuzian; theories which enable a focus on the body, movement and place and which have not yet been widely shared or developed with the museum sector or explicitly connected to practice. This book outlines these theories in an accessible way, explaining their usefulness for conceptualising young children in museums and connecting them to practical examples of programming in a range of locations via a series of contributed case studies. Connecting theory to practice for readers in a way that emphasises possibility, Working with Young Children in Museums should be essential reading for museum practitioners working in a range of institutions around the world. It should be of equal interest to researchers and students engaged in the study of museum learning, early childhood education and children's experiences in museums.
OCLC-licensed vendor bibliographic record.
Keywords: Museums -- Educational aspects; Museums and children; SOCIAL SCIENCE / Children's Studies; EDUCATION / General